2016
DOI: 10.1002/nau.22955
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for frequency volume chart and uroflowmetry parameters in adolescent and adult enuresis patients

Abstract: Both small MVV and NP were found frequently in our adolescent and adult enuresis patients, which is in line with the current thoughts on causal factors. NP prevalence is quite different when using ICS or ICCS definitions, respectively. We would like to encourage the development of an unambiguous definition of NP to use both in pediatric and adult urology. Neurourol. Urodynam. 36:463-468, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Hofmeester et al . [27] suggested that amongst patients with NE aged 11–42 years, 42% and 96% had small maximum voided volume and NP, respectively. In addition to previous knowledge, our present study has shown that men with NE can possess both or either increased urine production and bladder function problems, with reduced NBC, and NP with reduced NBC, to be independent predictors of NE episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Hofmeester et al . [27] suggested that amongst patients with NE aged 11–42 years, 42% and 96% had small maximum voided volume and NP, respectively. In addition to previous knowledge, our present study has shown that men with NE can possess both or either increased urine production and bladder function problems, with reduced NBC, and NP with reduced NBC, to be independent predictors of NE episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, a UFM with PVR evaluation was performed only once. It has been recognized that UFM requires repetition to improve its accuracy, reliability, and correct interpretation.- 6,13 Finally, we did not confirm whether FBC increased after treatment.…”
Section: Discussionmentioning
confidence: 70%
“…In children with NE, the evaluation of FBC can provide an important information about NP and bladder capacity. 13 ICCS recommends the use of 48-h F/V charts for this assessment. During this test, the volume and timing of all voids and fluid intake must be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the largest uroflowmetry void for analyses. Descriptions of adapted DBT, data‐collection, baseline characteristics and reference values for FVCs and uroflowmetry have been published in detail; 34% females, 65% primary enuresis, 81% non‐monosymptomatic enuresis, and 46% frequent enuresis (≥4 wet nights/week).…”
Section: Methodsmentioning
confidence: 99%